Establishment of a primary renal lymphoma model and its clinical relevance - Li, Xiaoxi; Deng, Minyao; Zhang, Chenxiao; Luo, Lingli; Qian, Hui (Frontiers in Oncology, 2023)
Extranodal dissemination is an important feature of aggressive B-cell lymphoma. Owing to the lack of available animal models, the study on extranodal dissemination of lymphoma is greatly limited. Here, we identified a novel cell line, named MA-K, which originated from the Eμ-Myc;Cdkn2a−/− cell line, named MA-LN in this study. Compared to MA-LN, MA-K tended to disseminate in the kidney rather than the lymph nodes in the lymphoma transplantation model, resembling human primary renal lymphoma. The transcriptome analysis revealed that MA-K had undergone transcriptional evolution during the culture. The specialized transcriptional pattern analysis we proposed in this study identified that the FOXO1-BTG1-MYD88 pattern was formed in MA-K. Further analysis found that the translation pathway was the most enriched pathway in specially expressed genes (SEGs) in MA-K. Among the SEGs, three upregulated genes, RPLP2, RPS16, and MRPS16, and five downregulated genes, SSPN, CD52, ANKRD37, CCDC82, and VPREB3, in MA-K were identified as promising biomarkers to predict the clinical outcomes of human DLBCL. Moreover, the joint expression of the five-gene signature could effectively predict clinical outcomes of human DLBCL in three groups. These findings suggested that the MA-K cell line had strong clinical relevance with human aggressive B-cell lymphoma. Moreover, the MA-K primary renal lymphoma model, as a novel syngenetic mouse model, will be greatly useful for both basic research on lymphoma dissemination and preclinical efficacy evaluation of chemotherapy and immunotherapy.